The Relationships Between Job Embeddedness, Person-Organization Fit, and Turnover Intention - Albertha Haga Ciptaningtyas; P. Tommy Y. S. Suyasa; Linda Wati (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2017)
This study aim to examine the relationships between job embeddedness, person-organization fit (POF), and turnover intention. Job embeddedness is a variety of conditions that make individuals feel attached to their job and organization. Person-organization fit is the compatibility between the characteristics of individuals and their organizations. Turnover intention is an employee’s conscious desire to leave his or her organization. This study was conducted among employees of a retail company in West Jakarta. The number of participants in this study was 177 employees. Data analysis was performed using Spearman correlation. Results show that job embeddedness was related to person-organization fit and turnover intention. However, there was no relationship between turnover intention and person-organization fit.